A Celtic warrior grave from Slatina v Rožni dolini near Celje? - Gaspari, Andrej; Krempuš, Robert; Brišnik, Danijela (Arheološki vestnik, 2004)
The article discusses 14 iron objects, kept by a local collec-tor in Velenje, which are supposed to have come from an asyet unknown Celtic warrior grave at Slatina v Rožni dolini nearCelje. A sword with a scabbard, a belt set, a shorter spear head,a shield umbo, scissors, a razor, and fibulae form a character-istic inventory of a male burial from the late phase of the middleLa Tène period (LT C2), and corresponds well both with thechronology and the forms of the other material from Slatina.Among the objects, which display a similar degree of patinaand preservation, stand out an slashing knife (Hiebmesser)with a rivet, the first such find in the territory of the Mokro-nog Group, a decorated curved knife, and a forked tool, whichprimarily have analogies in the late La Tène graves from theregion of the Scordisci, as well as a longer spear head. Thepossibility cannot be excluded that some of the objects couldhave been excavated from later burials, but they could alsocome from illegal excavations in the Danubian basin